Colon Classification: Notational System: Towards a Plan Tor its Productive Use - Ranganathan, S. R. (Journal of Information and Knowledge, 1972)
Sections a to h and j to y recapitulate the terminology in use, the progress made in the theory of Library Classification, and the increase in the versatility of the Notational System of CC. Sections 1 to 8 emphasise the need for a planned use of the rich versatility of the notational system. Sections A to D centre round a new method of design of classification, using Push- Bicycle as an illustration. Sections E to L mention some features of the new method of design used in Sec A7. Sections M to S consider the allocation of Sectors to different levels of (1P), and the advantages thereof. Sections T to Y emphasise the need for cooperation between DRTC and the librarians of Industrial Houses in applying the new method of design for constructing Depth Schedules for the classification of commodities and their parts.